Simulation Analysis of Cross-axis Magnetic Gear Characteristic - Wei Jie; Huiqing Lan (Jixie chuandong)
Cross-axis magnetic gears have a good application prospect in the industrial and aerospace fields. The advantage compared with mechanical gears is that the 90° space interleaving between the output and the input can be achieved by the one-stage transmission. In order to improve the feasibility of the cross-axis magnetic gear application， based on its structure and working principle， the finite element model of the cross-axis magnetic gear is established. The transient magnetic field is used for simulation analysis， then the influence of gear meshing clearance， number of magnetic pole， magnetic ring thickness， gear size， helix angle and width-to-diameter ratio on the maximum transmission torque of magnetic gear is obtained. Finally， the optimized structure of the cross-axis magnetic gear and its magnetic induction intensity cloud map are obtained. The results show that the reasonable structure and working characteristics of the cross-axis magnetic gear can be obtained by simulation， and the larger torque and better magnetic induction distribution can be obtained. The simulation results can provide a reference to structure design and the working characteristics analyze of the cross-axis magnetic gear， and greatly shorten its design and development cycle.